Modeling and Optimization of Spinning Parameters on Selectivity of Polysulfone Hollow Fiber Membrane for CO2/CH4 Separation - Mat Darus, Intan Zaurah; Khademi, Shahab; Mailah, Musa; Jye, Lau Woei; Khademi, Alireza (Makara Journal of Technology, 2021)
Hollow fiber membrane (HFM) and related technologies have recently become highly in demand and widely used in most industries and other areas recently. HFM could be used in different functions, from water and gas treatment to blood and medical applications. The paper describes the modeling of the effects of the spinning condition of a nonporous HFM on the membrane’s characteristics with the use of an automated hollow fiber fabrication system. An integrated, systematic experimental strategy based on the design of experiments was used to elaborate the effects of each parameter on selectivity. To obtain and sustain a satisfactory, significant selectivity of HFM, an automated system controlled the parameters during the fabrication process. The parameters involved in the fabrication of HFM and used in modeling are dope flow rate, bore flow rate, draw force, and air gap, which are considered inputs to fabricate polysulfone membrane. The fabrication process is improved by automating and instrumenting fabrication systems. An empirical model of the effects of fabrication parameters on the selectivity of the membrane is extracted experimentally. The mathematical model effectively explains the selectivity of CO2/CH4 with 95% fit.